Second case report of successful electroconvulsive therapy for a patient with schizophrenia and severe hemophilia A - Saito, Nobuyoshi (Dove Medical Press, 2014)
Electroconvulsive therapy (ECT) is used for medication-resistant and life-threatening mental disorders, and therefore it occupies an important position in psychiatric treatment. ECT reportedly increases intracranial pressure and is suspected of increasing the risk of intracranial hemorrhage, especially in patients with hemorrhagic diseases such as hemophilia. A decrease in or loss of blood coagulation factors, including factor VIII and factor IX, are found in hemophilia A and B, respectively. Psychiatrists may hesitate to perform ECT on patients with bleeding tendencies, such as in hemophilia. Here, we report the successful use of ECT on a neuroleptic-resistant patient with schizophrenia and severe hemophilia A. We performed ECT 16 times supplemented with coagulation factor VIII to prevent intracranial and systematic hemorrhage. We administered factor VIII concentrates to the patient to keep factor VIII activity at 30%–40% during ECT. The patient did not show bleeding or other complications during the ECT sessions. We suggest that pretreatment with factor VIII can help manage the increased risks of intracranial and systematic bleeding during ECT that is present in patients with hemophilia A. The present report supports the idea of performing ECT safely on patients with hemophilia A by administering factor VIII.